Trends and research patterns of blended learning in science education: A VOSviewer-based bibliometric analysis - Mastuang Mastuang; Misbah Misbah; Rossy Arlinda; Nurlaela Muhammad; Muhdi Harto; Qamariah Qamariah; Mazlena Binti Murshed (Education and Development Research, 2025)
Blended learning combines online and face-to-face, creating a dynamic and interactive learning environment. This article aims to provide a comprehensive bibliometric literature review on